Guanidiniocarbonyl Pyrrole Cation (GCP) – A New Guest for Cucurbit[8]uril: Application to the Synthesis of Supramolecular Polymers Based on CB[8]@2GCP Complex Formation. Issue 46 (20th November 2018) - Samanta, Krishnananda; Sicking, Wilhelm; Schmuck, Carsten
Abstract : Herein we introduce a new guest, the guanidiniocarbonyl pyrrole cation (GCP), for host–guest chemistry with cucurbit[8]uril. Macromodel calculations as well as isothermal titration calorimetry (ITC), showed that CB[8] can entrap two GCP molecules inside its hydrophobic cavity. Using this 1:2‐complex formation, we further show that CB[8] can induce crosslinking of a flexibletetracationic guanidiniocarbonyl pyrrole. An extended supramolecular cross‐linked 3D network was observed at pH 4.1 where all GCP groups in guanidiniocarbonyl pyrrole are protonated. At pH 6.5, the GCP groups are only partially protonated nanostructures with a more globular vesicle‐like shape. Abstract : Cucurbituril[8] is an efficient host for two GCP cations. Addition of CB[8] to a tetra‐GCP compound1 thus induces supramolecular polymerization. Depending on the pH and the protonation state of the GCP cation different types of aggregates are formed.